Marine invertebrate and seaweed biodiversity of continental coastal Ecuador - Cárdenas Calle, Maritza (2020)
This study summarises the diversity of living macroinvertebrates and seaweeds from the intertidal and subtidal rocky shores along Ecuadorian continental coast. Benthic macroinvertebrate communities and seaweeds were quantified over quadrants (50 × 50 cm) randomly placed on transects of 50 m length. A checklist of 612 species was generated: 479 species of macroinvertebrates and 133 species of seaweeds. Groups recorded were Mollusca (184 species), Cnidaria (70), Arthropoda (68), Annelida (60), Echinodermata (42), Chordata (18), Bryozoa (13), Porifera (22), Sipuncula (2), Brachiopoda and Platyhelminthes (only identified as morphotypes). The seaweeds were represented by Rhodophyta (78), Chlorophyta (37), Ochrophyta (13), Cyanobacteria (5) and 19 biotic complexes. Furthermore, 22 new taxa and six alien species were recorded from the intertidal zone. This study provides the first large scale report of benthic communities in different marine coastal ecosystems in mainland Ecuador, covering 1,478 km2 of protected areas and 382 km2 of non-protected areas. The highest benthic diversity was registered in the protected areas and rocky shores from the intertidal zone. The biological data, herein reported, are useful for a long-term monitoring programme to evaluate the status of conservation and to detect rapid changes in the benthic biodiversity from coastal areas.